An initial comparative genomic autopsy of wasting disease in sea stars. Issue 6 (17th March 2020) - Ruiz‐Ramos, Dannise V.; Schiebelhut, Lauren M.; Hoff, Katharina J.; Wares, John P.; Dawson, Michael N
Abstract: Beginning in 2013, sea stars throughout the Eastern North Pacific were decimated by wasting disease, also known as "asteroid idiopathic wasting syndrome" (AIWS) due to its elusive aetiology. The geographic extent and taxonomic scale of AIWS meant events leading up to the outbreak were heterogeneous, multifaceted, and oftentimes unobserved; progression from morbidity to death was rapid, leaving few tell‐tale symptoms. Here, we take a forensic genomic approach to discover candidate genes that may help explain sea star wasting syndrome. We report the first genome and annotation for Pisaster ochraceus, along with differential gene expression (DGE) analyses in four size classes, three tissue types, and in symptomatic and asymptomatic individuals. We integrate nucleotide polymorphisms associated with survivors of the wasting disease outbreak, DGE associated with temperature treatments in P. ochraceus, and DGE associated with wasting in another asteroid Pycnopodia helianthoides . In P. ochraceus, we found DGE across all tissues, among size classes, and between asymptomatic and symptomatic individuals; the strongest wasting‐associated DGE signal was in pyloric caecum. We also found previously identified outlier loci co‐occur with differentially expressed genes. In cross‐species comparisons of symptomatic and asymptomatic individuals, consistent responses distinguish genes associated with invertebrate innate immunity and chemical defence, consistent with context‐dependent stress responses, defensive apoptosis, and tissue degradation. Our analyses thus highlight genomic constituents that may link suspected environmental drivers (elevated temperature) with intrinsic differences among individuals (age/size, alleles associated with susceptibility) that elicit organismal responses (e.g., coelomocyte proliferation) and manifest as sea star wasting mass mortality.